Perancangan Program Aplikasi Kriptografi Menggunakan Algoritma Magenta dengan Panjang Kunci 128 Bit - Steffie Hugh Wibisono; Djunaidy Santoso (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Along with the development of computer technology, the growing crimes against the computer. Crimes against the computer makes people increasingly competing to make the algorithms-algorithms that can maintain the confidentiality of data. Algorithms algorithm Magenta is one of the many algorithms that exist today. Magenta algorithms have been developed since 1990 by using a simple and transparent technique that can be implemented in hardware and software. First time algorithms are analyzed using the butterfly structure - the structure of the butterfly which was then replaced by a Fast Hadamard Transform (FHT) shuffle structure which has the advantage of providing some structure in each level. In 1994 there was a slight change in the use of hardware that was not processed according to plan so that now the algorithm used by Deutsche Telekom Magenta for secure management of sensitive data with 128-bit key length. These algorithms break the 128-bit key length into 16 blocks with each block containing the 8-bit and one other advantage of this algorithm is the recursive part is calculated repeatedly at each iteration.